Certain Analytic Functions Defined by Generalized Mittag-Leffler Function Associated with Conic Domain. (9th June 2022) - Attiya, Adel A.; Seoudy, T. M.; Aouf, M. K.; Albalahi, Abeer M.
Abstract : In the present paper, we investigate and introduce several properties of certain families of analytic functions in the open unit disc, which are defined by q -analogue of Mittag-Leffler function associated with conic domain. A number of coefficient estimates of the functions in these classes have been obtained. Sufficient conditions for the functions belong to these classes are also considered.